MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Misra Misra; Rahima Zakiyah; zulvia trinova (Bajang Institute, 2022)
The purpose of this study is the planning, process, and evaluation of the implementation of the CTL learning model in the learning of Islamic Education at SMPN 31 Padang. The research method used is descriptive qualitative. The data source used is the primary data source of PAI teachers and students, secondary data sources namely the school principal. Data were collected using observation, interview, and documentation techniques and processed by reducing, presenting, and drawing conclusions. The results of the study are, educators have prepared learning in written form, namely the Learning Implementation Plan (RPP), curriculum, syllabus, and teaching materials. The process of implementing the CTL learning model, the teacher implements it according to the steps and characteristics contained in the PAI learning with the CTL model, the implementation of this learning is appropriate, but there are still shortages when the teacher applies it, the teacher still needs to improve the implementation of learning in terms of formulating goals, the teacher still often forget in conveying the learning objectives so that students are less purposeful in learning. Evaluation of the implementation of the CTL learning model in Islamic Religious Education learning at SMPN 31 Padang, according to its characteristics, reflects on this, it is done as feedback for the process of improvement and improvement of learning, including assessment in the form of tests.